Bridging the gap: improving CASPer test confidence and competency for underrepresented minorities in medicine through interactive peer-assisted learning - Shipeolu, Lolade; Matthieu, Johanne; Mahmood, Farhan; Okafor, Ike (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
Background: The Computer-based Assessment for Sampling Personal Characteristics (CASPer) is a situational judgement test (SJT) adopted by medical schools to assess applicants’ interpersonal skills. CASPer applicants must compose their responses to ethical dilemmas, thereby highlighting the applicant’s rationale for ethical decision-making. Minority applicants usually lack access to a network of individuals who can offer guidance and expertise on ethical decision-making. As such, this study investigated the impact of a CASPer coaching program designed for minority applicants.Methods: A free online intervention was designed to help minority applicants prepare for the CASPer test. The program consisted of 35 learners and three medical student tutors. Important attributes of the 4-week program included free access to a medical ethics book, feedback provision to in-class and homework student responses, and facilitation of a mock CASPer. Course feedback was collected. Additionally, a pre and post-program survey was administered to assess learners’ competence and confidence surrounding CASPer test-taking.Results: Our pre and post-program survey showed significant student improvement in familiarity with the test, increased competence, confidence and preparedness, as well as reduced anxiety (p < 0.05).Conclusions: Through peer-to-peer teaching and access to medical student mentors, our program addresses socioeconomic barriers that several minority applicants face when applying to medical school.